Metal-Free Synthesis of Selanyl-Substituted Chromenones via Selanylation/Cyclization of Alkynyl Aryl Ketones - Gong, Xi-Rui; Zhou, Yi-Huan; Ren, Mei-Lin; Chen, Yan-Yan; Xu, Yan-Li (Synthesis, 2024)
A variety of 2-substituted 3-selanyl-chromenones are readily prepared through a cascade selanylation/cyclization of alkynyl aryl ketones with sulfonoselenoates. This transformation is performed under metal-free conditions and does not require an additional oxidant. It also has the advantage of broad functional group tolerance and scalability.
Keywords: selanylation; 2-substituted 3-selanyl-chromenones; alkynyl aryl ketones; sulfonoselenoates; metal-free